2013
DOI: 10.1002/mren.201300146
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Bio‐Inspired Dry Adhesives: Van der Waals or Electrostatic Interactions?

Abstract: With respect to the dry adhesion mechanism that geckos employ for their locomotion, it is commonly accepted that the adhesive performance of synthetic bio‐inspired dry adhesives results from the formation of van der Waals interactions at the tip or side of the dry adhesive fibrils with the substrate they are brought into contact with. However, what has been usually neglected in this connection is that electrostatic interactions may also be developed at the contact between any two materials via the familiar con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 103 publications
(612 reference statements)
0
34
0
Order By: Relevance
“…Interestingly, simultaneous measurement of electric charges and adhesion forces revealed that CE-driven electrostatic interactions have a decisive contribution to the dry adhesion of geckos over these materials. Better insight into the role of CE-driven electrostatic interactions in gecko adhesion is not only very important for understanding the principles of the supreme adhesion of geckos [8,11], but also is fundamentally very crucial in the design and fabrication of synthetic fibrillar dry adhesives [12][13][14], which have been recently hypothesized to be largely affected by CE-generated electrostatic interactions [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, simultaneous measurement of electric charges and adhesion forces revealed that CE-driven electrostatic interactions have a decisive contribution to the dry adhesion of geckos over these materials. Better insight into the role of CE-driven electrostatic interactions in gecko adhesion is not only very important for understanding the principles of the supreme adhesion of geckos [8,11], but also is fundamentally very crucial in the design and fabrication of synthetic fibrillar dry adhesives [12][13][14], which have been recently hypothesized to be largely affected by CE-generated electrostatic interactions [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Electrostatic forces (Figure a) are similar to the van der Waals forces in essence . They are the attractive or repulsive forces between two surfaces with opposite or same charges .…”
Section: Theoretical Background and Progress Of The Peeling Modelmentioning
confidence: 96%
“…However, the adhesion mechanism of animals' hairy attachment organs continues to constitute a controversial matter. Although extant studies over several years confirmed that van der Waals interaction [6,7] and capillary forces [8,9] play dominant roles in setae adhesion, electrostatic attraction is increasingly invoked [10,11] to interpret the adhesion of hairy systems [9,10]. It is easy to positively tribo-electrify hair [12,13], and thus animals' hairy attachment organs are expected to become charged and subsequently generate electrostatic forces [10,14] as long as they interact with the environment to obtain forces to drive their locomotion.…”
Section: Introductionmentioning
confidence: 99%